Plan Nacional de Seguridad Ciudadana y Convivencia Social Pacífica y su relación con el Buen Vivir en la parroquia Urdaneta, cantón Saraguro, provincia de Loja en el año 2022 - Cabrera González, Diana Lizbeth (2024)
This research analyzed Plan Nacional de Seguridad Ciudadana y Convivencia Social Pacífica and its relationship with the Buen Vivir in the Urdaneta parish, Saraguro canton, Loja province in the year 2022, through the description of the elements that characterize the constitutional right of Buen Vivir and the actions carried out by the control agencies according to Plan Nacional de Seguridad Ciudadana y Convivencia Social Pacífica in the Urdaneta parish. Likewise, to identify the factors that generate citizen insecurity, as well as the elaboration of an action plan for the improvement of citizen security in accordance with the constitutional rights of Buen Vivir. In order to fulfill the proposed objectives, the research-action methodology was applied, the applied methods were deductive and analytical. The techniques applied were the survey conducted to the population of the neighborhoods that make up the Urdaneta parish, in an age range ranging from 20-64 years, giving a population of 310 people surveyed, in which it was possible to know the elements that characterize the constitutional right of Buen Vivir as established in the Plan, identifying the main factors that cause citizen insecurity such as high levels of unemployment and the low educational level of the inhabitants of the Urdaneta parish. Also, 3 authorities of the Urdaneta parish were interviewed to determine the actions carried out by the control agencies in accordance with the Plan; Once the results were analyzed, we moved on to the discussion where we compared and analyzed the theory of cognitive dissonance with the results obtained, and then gave way to the conclusions and recommendations.